Using computer simulation to understand and optimize high speed machining - Fischer, Christian E.; Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2003)
Presents the using of computer simulation in order to understand and optimize the high speed machining and to relate it with the latest technologies
Code no : DV03PUB78
Title from title screen
Recorded at the High Speed Machining Technical Conference, Apr. 8 & 9, 2003, Itasca, Ill.
Presenter: Christian E. Fischer
Keywords: High-speed machining -- Computer simulation; Machining